Alterations of the intrinsic amygdala‐hippocampal network in juvenile myoclonic epilepsy. Issue 8 (5th July 2021) - Lee, Dong Ah; Ko, Junghae; Lee, Ho‐Joon; Kim, Hyung Chan; Park, Bong Soo; Park, Sihyung; Kim, Il Hwan; Park, Jin Han; Lee, Yoo Jin; Park, Kang Min
Abstract: Introduction: Several lines of evidence suggest that the amygdala–hippocampus is involved in the epileptogenic network of juvenile myoclonic epilepsy (JME). The aim of this study was to investigate the alterations in the individual nuclei of the amygdala and hippocampal subfields, and the intrinsic amygdala‐hippocampal network of patients with JME compared to healthy controls. Methods: This retrospective study conducted at a single tertiary hospital involved 35 patients with newly diagnosed JME, and 34 healthy subjects. We calculated the individual structural volumes of 18 nuclei in the amygdala, and 38 hippocampal subfields using three‐dimensional volumetric T1‐weighted imaging and FreeSurfer program. We also performed an analysis of the intrinsic amygdala‐hippocampal global and local network based on these volumes using a graph theory and Brain Analysis using Graph Theory (BRAPH) program. We investigated the differences in these volumes and network measures between patients with JME and healthy controls. Results: There were no significant volume differences in the nuclei of the amygdala and hippocampal subfields between patients with JME and healthy controls. However, we found significant differences in the global network between patients with JME and healthy controls. The mean clustering coefficient was significantly decreased in patients with JME compared to healthy controls (0.473 vs. 0.653, p  = .047). In addition, specific regions in the hippocampal subfields showed significant differences in the local network between the two groups. The betweenness centrality of the right CA1‐head, right hippocampus–amygdala‐transition area, left hippocampal fissure, left fimbria, and left CA3‐head, was increased in patients with JME compared to healthy controls. Conclusion: The intrinsic amygdala‐hippocampal global and local networks differed in patients with JME compared to healthy controls, which may be related to the pathogenesis of JME, and memory dysfunction in patients with JME. Abstract : We investigate the alterations in the individual nuclei volume of amygdala and hippocampal subfields in JME. We also analyze intrinsic amygdala‐hippocampal network in JME. There are no volume differences in the nuclei of the amygdala and hippocampal subfields but significant differences in the global and local networks between patients with JME and healthy controls exist.